Aqueous sodium ion secondary battery

By using sodium-containing transition metal polyanions as the positive electrode active material in aqueous sodium ion secondary batteries and combining with aqueous electrolytes, the problem of low electrochemical capacity of existing batteries is solved and a higher electrochemical capacity is achieved.

CN113939931BActive Publication Date: 2025-02-14KYUSHU UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080039090.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-27
Filing Date
2020-05-27
Publication Date
2025-02-14
Estimated Expiration
2040-05-27

AI Technical Summary

Technical Problem

The electrochemical capacity of the existing aqueous sodium ion secondary batteries is relatively low, and it is difficult to reach a high level compared with the previously known aqueous electrolytes.

Method used

The aqueous sodium ion secondary battery is formed by using a sodium-containing transition metal polyanion containing three Na cations as the positive electrode active material, combined with an aqueous electrolyte. The general formula of the positive electrode active material is Na3-xMPO4CO3, wherein M is at least one of Fe, Mn, Ni or Co, and x is 0 or more and 2 or less.

Benefits of technology

The electrochemical capacity of the aqueous sodium ion secondary battery is significantly improved, so that it exhibits a higher capacity compared to the previously known aqueous electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113939931B_ABST
    Figure CN113939931B_ABST
Patent Text Reader

Abstract

The present invention provides an aqueous sodium ion secondary battery, which can exhibit a high electrochemical capacity compared with a sodium ion secondary battery having a conventionally known aqueous electrolyte. The aqueous sodium ion secondary battery is characterized in that it comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode has at least a general formula Na 3‑x A positive electrode active material of a sodium transition metal polyanion represented by MPO4CO3 (M is at least one selected from Fe, Mn, Ni and Co, and x is greater than or equal to 0 and less than or equal to 2), having an aqueous electrolyte as the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of secondary batteries, and in particular relates to aqueous sodium ion secondary batteries. Background Art

[0002] Sodium ion secondary batteries do not use lithium, which is a rare metal, and therefore have attracted much attention as post-lithium ion secondary batteries. As sodium ion secondary batteries, research has focused on batteries that have the same electrolyte as existing lithium ion secondary batteries, mainly non-aqueous electrolytes. On the other hand, research has focused on sodium ion secondary batteries that use aqueous electrolytes as electrolytes, which use inexpensive water.

[0003] Patent Document 1 and Non-Patent Document 1 confirm that charging and discharging based on reversible insertion and extraction reactions of Na cations occur in sodium ion secondary batteries having an aqueous electrolyte. The electrochemical capacity of these sodium ion secondary batteries during initial charge and discharge is approximately 120 mAh / g.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-520383

[0007] Non-patent literature

[0008] Non-patent document 1: H. Chen et al., Chemistry of Materials, 25, 2777-2786 (2013) Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] An object of the present invention is to provide an aqueous sodium ion secondary battery that can exhibit a higher electrochemical capacity than a sodium ion secondary battery having a conventionally known aqueous electrolyte.

[0011] Means for solving technical problems

[0012] The inventors have repeatedly conducted in-depth research on sodium ion secondary batteries with aqueous electrolytes (hereinafter referred to as "aqueous sodium ion secondary batteries"). As a result, it was found that by using sodium-containing transition metal polyanions containing three Na cations as positive electrode active materials, the aqueous sodium ion secondary batteries formed showed higher electrochemical capacity than the aqueous sodium ion secondary batteries known in the past.

[0013] That is, the gist of the present invention is as follows.

[0014] [1] An aqueous sodium ion secondary battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode has at least a general formula of Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by MPO4CO3 (M is at least one selected from Fe, Mn, Ni and Co, and x is greater than or equal to 0 and less than or equal to 2), wherein the aqueous sodium ion secondary battery has an aqueous electrolyte as the electrolyte.

[0015] [2] The aqueous sodium ion secondary battery according to [1] above, wherein carbon is present on part or all of the surface of the sodium transition metal polyanion.

[0016] [3] The aqueous sodium ion secondary battery according to [1] or [2], wherein the crystal particle size of the sodium transition metal polyanion is Above and the following.

[0017] [4] An aqueous sodium ion secondary battery according to any one of [1] to [3] above, wherein the aqueous electrolyte contains one or more selected from the group consisting of Na2SO4, NaNO3 and NaClO4.

[0018] [5] The aqueous sodium ion secondary battery according to any one of [1] to [4] above, wherein the aqueous electrolyte contains NaClO4.

[0019] [6] The aqueous sodium secondary battery according to [5] above, wherein the electrolyte concentration in the electrolyte solution is 5 mol / kg or more.

[0020] [7] An aqueous sodium ion secondary battery according to any one of [1] to [6] above, wherein the negative electrode comprises at least NaTi2(PO4)3.

[0021] [8] The aqueous sodium ion secondary battery according to any one of [1] to [7] above, wherein the positive electrode has at least one 3-x A positive electrode active material of a sodium transition metal polyanion represented by FePO4CO3 (x is greater than or equal to 0 and less than or equal to 2), wherein the negative electrode contains at least NaTi2(PO4)3, and the aqueous electrolyte contains at least NaClO4.

[0022] [9] A positive electrode active material for an aqueous sodium ion secondary battery, comprising at least 3-x A sodium transition metal polyanion represented by MPO4CO3 (M is at least one selected from Fe, Mn, Ni and Co, and x is greater than or equal to 0 and less than or equal to 2).

[0023]

[10] The positive electrode active material for an aqueous sodium ion battery according to [9] above, wherein M contains at least Fe.

[0024] Effects of the Invention

[0025] According to the present invention, it is possible to provide an aqueous sodium ion secondary battery that can exhibit a higher electrochemical capacity than a sodium ion secondary battery having a conventionally known aqueous electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of a sodium-ion secondary battery (half-cell).

[0027] Figure 2 It is a schematic diagram of a sodium-ion secondary battery (button battery).

[0028] Figure 3 These are the charge and discharge curves of the first cycle and the second cycle of Example 1.

[0029] Figure 4 These are the charge and discharge curves of the first cycle and the second cycle of Example 2.

[0030] Figure 5 These are the charge and discharge curves of the first cycle and the second cycle of Example 3.

[0031] Figure 6 These are the charge and discharge curves of the first cycle and the second cycle of Example 4.

[0032] Figure 7 These are the charge and discharge curves of the first cycle and the second cycle of Example 5.

[0033] Figure 8 These are the charge and discharge curves of the first cycle and the second cycle of Reference Example 1. DETAILED DESCRIPTION

[0034] Hereinafter, preferred embodiments of the aqueous sodium ion secondary battery of the present invention will be described. It should be noted that, hereinafter, the terms sodium ion secondary battery, sodium secondary battery, and sodium ion battery are used with the same meaning.

[0035] The positive electrode of the aqueous sodium ion secondary battery of this embodiment has at least a general formula of Na 3-xA positive electrode active material of a sodium transition metal polyanion (hereinafter referred to as "Na polyanion") represented by MPO4CO3 (M is at least one selected from Fe, Mn, Ni and Co, and x is greater than 0 and less than 2). The Na polyanion is a sodium-containing transition metal phosphate carbonate, preferably an artificially synthesized sodium-containing transition metal phosphate carbonate. It functions as a positive electrode active material for an aqueous sodium ion secondary battery. In addition, the Na polyanion of the present embodiment is at least a general formula Na 3-x A positive electrode active material for an aqueous sodium ion secondary battery of a sodium transition metal polyanion represented by MPO4CO3 (M is at least one selected from Fe, Mn, Ni and Co, and x is greater than or equal to 0 and less than or equal to 2).

[0036] Here, M preferably contains at least Fe, more preferably at least one of Fe and Mn, and particularly preferably Fe. In addition, x may be 0 or more and 1 or less.

[0037] As specific Na polyanions, one or more selected from sodium iron carbonate phosphate, sodium manganese carbonate phosphate, sodium nickel carbonate phosphate and sodium cobalt carbonate phosphate can be exemplified, further one or more selected from sodium iron carbonate phosphate, sodium manganese carbonate phosphate and sodium cobalt carbonate phosphate can be exemplified, further at least any one of sodium iron carbonate phosphate and sodium manganese carbonate phosphate can be exemplified, and further sodium iron carbonate phosphate can be exemplified.

[0038] The physical properties of the Na polyanion are not particularly limited and can be appropriately adjusted in accordance with the target battery configuration. As physical properties, for example, crystal system, purity, lattice constant, crystallinity, grain size, crystal orientation, pore diameter, pore distribution, pore volume, BET specific surface area, primary particle size, secondary particle size, powder particle size, particle size distribution, particle morphology, and particle size composition can be cited, but are not limited thereto.

[0039] The crystal size of the Na polyanion is preferably Above and the following, Above and the following, Above and Below, or Above and Below. The grain size in the present embodiment is preferably a diameter obtained from an XRD spectrum and obtained by the Williamson-Hall method (hereinafter also referred to as "WH diameter"). The WH diameter is the grain size obtained from more than two XRD peaks attributable to Na polyanions in the XRD spectrum. Specifically, for more than two XRD peaks attributable to Na polyanions, the following plotting is performed for each. The following first-order approximation is obtained by the least squares method of the plotting of the obtained multiple points, and the inverse of the y intercept of the first-order approximation is the grain size.

[0040] <Drawing points>

[0041] Y=(β·sinθ) / λ

[0042] X=sinθ / λ

[0043] <First-order approximation>

[0044] Y=2η·X+(1 / ε) (Formula 1)

[0045] In these equations, β is the half-height width (°), θ is the diffraction angle (°), λ is the wavelength of the radiation source (nm), η is the inhomogeneous strain and ε is the grain size The 1 / ε in the linear approximation is the y intercept. 2η is equivalent to the slope of the linear approximation obtained by plotting the XRD peak.

[0046] Preferably, the WH diameter is the grain size obtained from the XRD peaks corresponding to the (020) plane, (220) plane and (002) plane in the XRD spectrum. Specifically, the above-mentioned plotting is performed for the XRD peaks corresponding to the (020) plane, (220) plane and (002) plane, respectively. The above-mentioned first-order approximation is obtained by the least square method of the plotted points of the obtained three points, and the inverse of the y-intercept of the first-order approximation is the grain size.

[0047] The XRD peaks corresponding to the (020) plane, (220) plane, and (002) plane of the Na polyanion in the present embodiment can be confirmed as XRD peaks having peak positions at the following 2θ (hereinafter also referred to as “main peak group”).

[0048] (020) plane: 2θ = 26.39° to 27.06°

[0049] (220) plane: 2θ = 33.19° to 33.88°

[0050] (002) plane: 2θ = 34.59° to 34.99°

[0051] The Na polyanion has the general formula Na 3-xIn the case of FePO4CO3 (sodium iron phosphate carbonate), the 2θ of the main peak group is preferably the following value, and the crystallite size is preferably Above and The following are particularly preferred Above and the following.

[0052] (020) plane: 2θ = 26.86° to 26.94°

[0053] (220) plane: 2θ = 33.56° to 33.69°

[0054] (002) plane: 2θ = 34.76° to 34.86°

[0055] The Na polyanion has the general formula Na 3-x In the case of MnPO4CO3 (in the case of sodium manganese phosphate carbonate), the 2θ of the main peak group is preferably the following value, and the crystallite size is preferably Above and The following are particularly preferred Above and the following.

[0056] (020) plane: 2θ = 26.39° to 26.47°

[0057] (220) plane: 2θ = 33.19° to 33.29°

[0058] (002) plane: 2θ = 34.59° to 34.77°

[0059] The Na polyanion has the general formula Na 3-x In the case of NiPO4CO3 (in the case of sodium nickel phosphate carbonate), the 2θ of the main peak group is preferably the following value, and the crystallite size is preferably Above and The following, particularly preferably Above and the following.

[0060] (020) plane: 2θ = 26.91° to 27.06°

[0061] (220) plane: 2θ = 33.68° to 33.88°

[0062] (002) plane: 2θ = 34.84° to 34.99°

[0063] The Na polyanion has the general formula Na 3-xIn the case of CoPO4CO3 (sodium cobalt phosphate carbonate), the 2θ of the main peak group is preferably the following value, and the crystallite size is preferably Above and The following, particularly preferably Above and the following.

[0064] (020) plane: 2θ = 26.88° to 26.94°

[0065] (220) plane: 2θ = 33.63° to 33.69°

[0066] (002) plane: 2θ = 34.84° to 34.88°

[0067] The XRD spectrum in this embodiment can be measured under the following conditions.

[0068] Radiation source: Cu Kα ray

[0069] Measurement mode: Step scan

[0070] Scanning condition: 20° / min

[0071] Measuring time: 3 seconds

[0072] 2θ: 5°~90°

[0073] The obtained XRD spectrum can be subjected to Rietvelt precision analysis using commercially available analysis software (such as data processing software PDXL-2 attached to an X-ray diffraction apparatus (such as SmartLab; manufactured by RIGAKU)) to characterize and analyze the crystal phase of the product.

[0074] The preferred crystal system of the Na polyanion belongs to the monoclinic crysal system. Further, the monoclinic crysal system preferably has a space group belonging to at least one of P21 / m and P21. The monoclinic crysal system to which the Na polyanion belongs is a crystal system in which the lattice constants a, b, and c are each different values, α and γ are both 90°, and β is an angle other than 90°.

[0075] The lattice constants of the Na polyanions in this embodiment are preferably: a is Above and Below, b is Above and Below, c is Above and α is 90.00°, γ is 90.00°, and β is 89.00° or more and 90.50° or less. More preferred lattice constants include: a is Above and Below, b is Above and Below, α is 90.00°, γ is 90.00°, c is Above and The following and β are 89.10° or more and 90.20° or less.

[0076] In this embodiment, the general formula Na 3-x The lattice constants of the Na polyanion represented by FePO4CO3 are: a is Above and The following, preferably Above and The following, more preferably Above and Below, b is Above and The following, preferably Above and The following, more preferably Above and Below, c is Above and The following, preferably Above and The following, more preferably Above and Below, α is 90.00°, γ is 90.00°, and β is 89.30° to 89.80°, preferably 89.50° to 89.70°.

[0077] In this embodiment, the general formula Na 3-x The lattice constants of the Na polyanion represented by MnPO4CO3 are: a Above and The following, preferably Above and The following, more preferably Above and The following is more preferably Above and Below, b is Above and The following, preferably Above and The following, more preferably Above and The following is more preferably Above and Below, c is Above and The following, preferably Above and The following, more preferably Above and Below, α is 90.00°, γ is 90.00°, β is 89.90° or more and 90.50° or less, preferably 90.10° or more and 90.20° or less, and more preferably 90.14° or more and 90.20° or less.

[0078] In this embodiment, the general formula Na 3-x The lattice constants of the Na polyanion represented by NiPO4CO3 are: a Above and The following, preferably Above and The following, more preferably Above and The following is more preferably Above and Below, b is Above and The following, preferably Above and The following, more preferably Above and Below, c is Above and The following, preferably Above and The following, more preferably Above and The following is more preferably Above and Below, α is 90.00°, γ is 90.00°, β is 89.00° to 89.40°, preferably 89.10° to 89.30°, more preferably 89.15° to 89.29°, further preferably 89.15° to 89.25°.

[0079] In this embodiment, the general formula Na 3-x The lattice constants of the Na polyanion represented by CoPO4CO3 are: a Above and The following, preferably Above and The following, more preferably Above and The following is more preferably Above and Below, b is Above and The following, preferably Above and The following, more preferably Above and Below, c is Above and The following, preferably Above and The following, more preferably Above and The following is more preferably Above and Below, α is 90°, γ is 90°, β is 89.20° to 89.65°, preferably 89.30° to 89.55°, more preferably 89.35° to 89.52°, further preferably 89.35° to 89.48°.

[0080] Preferably, a part or all of the Na polyanion has carbon, so that the conductivity is more easily improved. As the state that the Na polyanion has carbon (i.e., the carbon-coated Na polyanion), a part or all of the surface of the Na polyanion can be enumerated, for example, the Na polyanion has carbon in a sea island shape on at least a part of the surface of the Na polyanion or is covered with carbon.

[0081] The method of making Na polyanion into a state with carbon is arbitrary, and a method of mixing Na polyanion and carbon material can be exemplified. Carbon material is a precursor of carbon, and is at least any one of carbon and carbon compound with conductivity. The specific carbon material as a precursor of carbon can be exemplified by one or more selected from furnace black, channel black, acetylene black and thermal black, and further acetylene black and thermal black can be exemplified, and acetylene black can be further exemplified. The atmosphere during mixing is as long as it is an atmosphere that is not easy to damage the conductivity of the carbon material, preferably an inactive atmosphere. As an inactive atmosphere, the atmosphere of at least any one of nitrogen and argon can be cited. Regarding the mixing method of Na polyanion and carbon, as long as the Na polyanion can be made into a state with carbon on part or all of its surface, there is no particular limitation, preferably a method of mixing while crushing the carbon material, preferably a mixing method using a ball mill, and more preferably a mixing method using a planetary ball mill.

[0082] The Na polyanion having carbon on the surface (carbon-coated Na polyanion) can be subjected to annealing treatment, for example, carbon heat treatment in an inactive atmosphere. By performing these treatments, the electronic conductivity can be improved. 3-xIn the case of Na polyanions shown in FePO4CO3, carbon on the surface of the Na polyanion precipitates conductive iron phosphide as a reductant on the surface of the Na polyanion by carbon heat treatment, and it can also be considered that the contact resistance between Na polyanion particles is reduced. The method of carbon heat treatment is not particularly limited, and an example can be shown in which a method of treating Na polyanions having carbon on the surface for more than 1 hour and less than 12 hours at a temperature of more than 200°C and less than 700°C in an inactive atmosphere of at least one of nitrogen and argon can be shown.

[0083] In the case where the carbon-coated Na polyanion is subjected to carbon heat treatment, in addition to carbon materials such as acetylene black as a precursor of carbon, a compound that can be carbonized at least in part by thermal decomposition can also be used as a precursor. As such a compound, for example, alcohol, an organic compound can be enumerated, preferably more than one selected from cyclodextrin, ascorbic acid, glycolic acid, malic acid, citric acid, fructose and sucrose.

[0084] Na polyanions can be manufactured by any method. As a method for manufacturing Na polyanions, for example, a method of mechanically grinding a composition containing sodium, a transition metal, phosphoric acid and carbonic acid can be cited. Specifically, a method of mixing NaMPO4 (M is at least one selected from Fe, Mn, Ni and Co) and Na2CO3 and mechanically grinding them under an inactive atmosphere such as argon can be exemplified. Thus, solid-phase synthesized Na polyanions are obtained. As other methods for manufacturing Na polyanions, for example, a method of hydrothermally treating a composition containing a sodium source, a transition metal source, a phosphoric acid source, a carbonate source and water can be cited; a preferred manufacturing method is characterized in that it has a step of hydrothermally treating a composition containing a sodium source, a transition metal source, a phosphoric acid source, a carbonate source and water, the hydrothermal treatment temperature is above 140°C and below 280°C, and the pH of the composition is above 7.5; more preferably, the composition contains two or more water-soluble sodium salts. Thus, liquid-phase synthesized Na polyanions are obtained. Specifically, there can be exemplified a method of hydrothermally treating a composition having a pH of 7.5 to 10.0 and containing a transition metal sulfate, sodium phosphate, anhydrous sodium carbonate and water at a temperature of 160° C. to 250° C. in an autogenous pressure atmosphere.

[0085] The positive electrode of the aqueous sodium ion secondary battery of the present embodiment only needs to contain Na polyanions as the positive electrode active material. The content of Na polyanions in the positive electrode active material is measured by the weight ratio of Na polyanions in the weight of the positive electrode active material, preferably 80% by mass or more and 100% by mass or less, more preferably 90% by weight or more and 100% by weight or less, and particularly preferably 100% by weight (the positive electrode active material is only Na polyanions, that is, it does not substantially contain active materials other than Na polyanions). In addition, in the positive electrode, as a positive electrode mixture comprising a positive electrode active material and at least one selected from a binder and a conductive material, Na polyanions may be included. Binders and conductive materials can use known substances. For example, the binder can include one or more of fluorine resins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene (ETFE), polyethylene, polypropylene, SBR materials and imide materials, and the conductive material can include one or more of organic conductive materials such as conductive fibers such as carbon materials, metal fibers, copper, silver, nickel, aluminum, and metal powders, polyphenylene derivatives. It should be noted that the carbon material as a conductive material can illustrate graphite, soft carbon, hard carbon, carbon black, Ketjen black, acetylene black, graphite (graphite), activated carbon, carbon nanotubes, carbon fibers, synthetic resins containing aromatic rings, petroleum-based asphalt, etc., calcined and obtained mesoporous carbon, but is not limited thereto. As a specific positive electrode mixture, it can be illustrated that at least one of Na polyanions, PVDF and PTFE, and one or more positive electrode mixtures selected from graphite, graphite (graphite), soft carbon, hard carbon and acetylene black.

[0086] The positive electrode mixture can be produced by any method as long as the Na polyanion, the binder, and the conductive material are mixed by any method at a ratio suitable for the target positive electrode mixture.

[0087] The aqueous sodium ion secondary battery of the present embodiment has an aqueous electrolyte as an electrolyte. The aqueous electrolyte contains water and an electrolyte as a solvent. The electrolyte can be any water-soluble sodium salt, and one or more selected from Na2SO4, NaNO3, NaClO4 and NaOH can be exemplified. From the perspective of ease of handling, the electrolyte is preferably one or more selected from Na2SO4, NaNO3 and NaClO4, and more preferably NaClO4. The electrolyte concentration in the electrolyte is not particularly limited. From the perspective of improving the energy density of the sodium ion secondary battery, the electrolyte concentration (sodium salt concentration) in the electrolyte is preferably high. As a sodium salt concentration, 2 mol / L or more can be exemplified, and a concentration below the saturated solubility can be cited. In the case of using NaClO4 as an electrolyte, the electrolyte concentration (NaClO4 concentration) in the electrolyte can be exemplified as 5 mol / kg or more, 7 mol / kg or more, or 10 mol / kg or more, and 17 mol / kg or less.

[0088] In order to optimize the physical properties and characteristics of the electrolyte such as storage stability and battery characteristics, the electrolyte may contain additives. As additives, for example, succinic acid, glutamic acid, maleic acid, citraconic acid, gluconic acid, itaconic acid, diethylene glycol, cyclohexanedicarboxylic acid, cyclopentanetetracarboxylic acid, 1,3-propane sultone, 1,4-butane sultone, methyl methanesulfonate, cyclopentane sulfone, dimethyl sulfone, N,N-dimethylmethanesulfonamide, etc. can be illustrated, but are not limited thereto. The content in the electrolyte is preferably 0.01 to 10% by weight.

[0089] The negative electrode of the sodium ion secondary battery of the embodiment is a negative electrode active material. In a sodium ion secondary battery with an aqueous electrolyte, it is sufficient to include a material that does not hinder the absorption and release of sodium ions of the positive electrode active material. As the negative electrode active material, for example, one or more selected from platinum, zinc, carbon materials, materials forming alloys with sodium, sodium-containing transition metal oxides and sodium-containing polyanion materials can be cited, preferably one or more selected from carbon materials, polyimides, transition metal-containing cyanides and transition metal-containing polyanion compounds. As specific various negative electrode active materials, activated carbon can be cited as a carbon material, Na2Mn[Mn(CN)6] can be cited as a transition metal-containing cyanide, and NaTi2(PO4)3 can be cited as a transition metal-containing polyanion compound. As a particularly preferred negative electrode active material, NaTi2(PO4)3 can be cited.

[0090] In the negative electrode of the aqueous sodium ion secondary battery of the present embodiment, as a negative electrode mixture comprising a negative electrode active material and at least one selected from a binder and a conductive material, a negative electrode active material may be included. The binder and the conductive material may use known substances, and for example, the same binder and conductive material as those that can be used in the above-mentioned positive electrode mixture can be cited. The negative electrode mixture can be manufactured by any method, and the negative electrode active material, the binder and the conductive material are mixed in a ratio suitable for the target negative electrode mixture.

[0091] As other components of the aqueous sodium ion secondary battery such as the current collector, components used for a known sodium ion secondary battery can be used.

[0092] The aqueous sodium ion secondary battery of this embodiment comprises a positive electrode, a negative electrode, and an aqueous electrolyte, wherein the positive electrode has at least a general formula of Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by MPO4CO3 (M is 1 or more selected from Fe, Mn, Ni and Co, and x is 0 or more and 2 or less), wherein the negative electrode contains at least NaTi2(PO4)3, and the aqueous electrolyte contains at least NaClO4.

[0093] Furthermore, the aqueous sodium ion secondary battery of another embodiment of the present invention comprises a positive electrode, a negative electrode, and an aqueous electrolyte, wherein the positive electrode has at least a general formula of Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by MPO4CO3 (M is one or more selected from Fe, Mn and Co, and x is greater than 0 and less than 2), wherein the negative electrode contains at least NaTi2(PO4)3, and the aqueous electrolyte contains at least NaClO4.

[0094] Furthermore, the aqueous sodium ion secondary battery of another embodiment of the present invention comprises a positive electrode, a negative electrode, and an aqueous electrolyte, wherein the positive electrode has at least a general formula of Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by MPO4CO3 (M is Fe or Mn, x is greater than 0 and less than 2), wherein the negative electrode contains at least NaTi2(PO4)3, and the aqueous electrolyte contains at least NaClO4.

[0095] More preferably, the aqueous sodium ion secondary battery of the present embodiment comprises a positive electrode, a negative electrode, and an aqueous electrolyte, wherein the positive electrode has at least a general formula Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by MnPO4CO3 (x is greater than or equal to 0 and less than or equal to 2), wherein the negative electrode contains at least NaTi2(PO4)3, and the aqueous electrolyte contains at least NaClO4.

[0096] Furthermore, the aqueous sodium ion secondary battery of another embodiment of the present invention comprises a positive electrode, a negative electrode, and an aqueous electrolyte, wherein the positive electrode has at least a general formula of Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by FePO4CO3 (x is greater than or equal to 0 and less than or equal to 2), wherein the negative electrode contains at least NaTi2(PO4)3, and the aqueous electrolyte contains at least NaClO4.

[0097] Example

[0098] Hereinafter, the present embodiment will be described in detail with reference to examples, but the present embodiment is not limited to these examples.

[0099] <Characterization of Na polyanion>

[0100] The XRD spectrum of the Na polyanion obtained in the synthesis example was measured under the following conditions.

[0101] Radiation source: Cu Kα ray

[0102] Measurement mode: Step scan

[0103] Scanning condition: 20° / min

[0104] Measuring time: 3 seconds

[0105] 2θ: 5°~90°

[0106] The obtained XRD spectrum was subjected to Rietvelt precision analysis using data processing software PDXL-2 attached to an X-ray diffractometer (device name: SmartLab; manufactured by RIGAKU) to characterize and analyze the crystal phase of the product.

[0107] <Manufacturing of sodium-ion secondary battery (half-cell)>

[0108] The weight ratio of Na polyanion to acetylene black (AB) is 70:30, and a planetary ball mill is used to perform carbon coating treatment at 400-500 rpm, 9 hours, and Ar atmosphere to obtain a positive electrode active material composed of a powdered Na polyanion (carbon-coated Na polyanion) with carbon covering the surface. The obtained positive electrode active material is mixed with AB and PTFE in a weight ratio of 60:30:10 to obtain a granular positive electrode mixture with a diameter of 10 mm. The positive electrode mixture is used as the working electrode (positive electrode), a plate-shaped zinc metal (Zn) is used as the counter electrode (negative electrode), a silver chloride electrode (Ag / AgCl) is used as the reference electrode, and a 17M (17 mol / kg) NaClO4 aqueous solution is used as the electrolyte to produce Figure 1 The beaker-type half-cell sodium-ion secondary battery shown.

[0109] <Manufacturing of sodium-ion secondary batteries (button batteries)>

[0110] (Production of negative electrode)

[0111] As the negative electrode active material, NaTi2(PO4)3 synthesized by the Pechini method shown below is used. First, 40 ml of a solution of Ti(OCH2CH2CH2CH3)4 dissolved in a 30% hydrogen peroxide solution, 15 ml of 28% ammonia water, 10 ml of a nitric acid solution of citric acid with a molar amount of Na2CO3 and 2 times that of Ti, 10 ml of an aqueous solution of NH4H2PO4, and ethylene glycol are mixed, and the resulting mixed solution is evaporated and dried at 80°C for 1 to 2 hours. After that, it is heated at 140°C in the atmosphere to obtain a brown gel-like composition. After calcining it at 350°C in the atmosphere, it is calcined at 800°C in the atmosphere to obtain NaTi2(PO4)3.

[0112] The obtained NaTi2(PO4)3 was mixed with AB in a weight ratio of 70:25 using a planetary ball mill at 400 rpm for 1 hour, and carbon-coated to obtain a negative electrode active material consisting of powdered NaTi2(PO4)3 with carbon on the surface. The obtained negative electrode active material was mixed with PTFE in a weight ratio of 95:5, and formed into a pellet with a diameter of 10 mm, which was used as a negative electrode mixture.

[0113] (Button battery production)

[0114] The positive electrode and negative electrode were prepared by using a positive electrode mixture prepared by the same method as the positive electrode mixture used in the half-cell and the above-mentioned negative electrode mixture, respectively, and a 17M NaClO4 aqueous solution was used as the electrolyte. Figure 2 The button cell type sodium ion secondary battery shown in the figure has a positive electrode and a negative electrode in the sodium ion secondary battery, with a weight ratio of positive electrode active material to negative electrode active material of 1:1.5.

[0115] <Synthesis of Na polyanion>

[0116] Synthesis Example 1 (Synthesis of Sodium Iron Phosphate Carbonate)

[0117] After ferrous sulfate heptahydrate (FeSO4·7H2O), sodium phosphate 12hydrate (Na3PO4·12H2O) and anhydrous sodium carbonate (Na2CO3) were pulverized and mixed, pure water was added thereto to obtain a composition having the following composition.

[0118] Ferrous sulfate heptahydrate: 13.6 wt%

[0119] Sodium phosphate 12 hydrate: 18.7% by weight

[0120] Anhydrous sodium carbonate: 5.2% by weight

[0121] Pure water: Balance

[0122] The pH of the composition was 11.0. The composition was filled and sealed in a container with a lid made of Teflon (registered trademark) resin, and then placed in a thermostatic bath to perform a hydrothermal treatment under the following conditions.

[0123] Hydrothermal treatment temperature: 180℃

[0124] Hydrothermal treatment time: 16 hours

[0125] Hydrothermal treatment pressure: under autogenous pressure

[0126] After the hydrothermal treatment, a sufficient amount of pure water was added to the product cooled to room temperature and stirred to wash the product. The product was then suction filtered using a filter paper having a pore size of 0.2 μm to obtain sodium iron carbonate phosphate.

[0127] The obtained sodium iron carbonate phosphate was dried at 110°C for 4 hours under vacuum and then crushed in a mortar to obtain the sodium iron carbonate phosphate of this synthesis example. The purity of the sodium iron carbonate phosphate Na3FePO4CO3 of this synthesis example is 100% by weight, and no crystallized products other than Na3FePO4CO3 are confirmed in its XRD spectrum. The Na3FePO4CO3 of this synthesis example has a grain size (WH diameter) of The lattice constant is a b is c is The compound has α of 90.00°, β of 89.58°, and γ of 90.00°, a monoclinic crystal system, a bonshtedtite structure, and belongs to the space group P21 / m. The main XRD peaks are shown below.

[0128] (020) plane: 2θ = 26.86° relative intensity = 81

[0129] (220) plane: 2θ = 33.57° relative intensity = 78

[0130] (002) plane: 2θ = 34.80° relative intensity = 100

[0131] Synthesis Example 2 (Synthesis of Sodium Iron Phosphate Carbonate)

[0132] Sodium carbonate (Na2CO3) and sodium iron phosphate (iron salt (malysite) NaFePO4) were mixed in a stoichiometric ratio of 1:1, and then mixed in a planetary ball mill under the conditions of Ar atmosphere, 600 rpm, and 12 hours. AB was added to the obtained powder in a manner to achieve a weight ratio of 15wt%, and mixed in a planetary ball mill under the conditions of Ar atmosphere, 600rpm, and 12 hours. AB was further added in a manner to achieve a weight ratio of 15wt%, and mixed in a planetary ball mill under the conditions of Ar atmosphere, 400rpm, and 3 hours, to obtain sodium iron phosphate carbonate Na3FePO4CO3.

[0133] Synthesis Example 3 (Synthesis of Sodium Manganese Phosphate Carbonate)

[0134] Manganese sulfate pentahydrate (MnSO4.5H2O), sodium phosphate 12 hydrate (Na3PO4.12H2O) and anhydrous sodium carbonate (Na2CO3) were pulverized and mixed, and then pure water was added thereto to obtain a composition having the following composition.

[0135] Manganese sulfate pentahydrate: 12.0 wt%

[0136] Sodium phosphate 12 hydrate: 18.9 wt%

[0137] Anhydrous sodium carbonate: 5.2% by weight

[0138] Pure water: Balance

[0139] The pH of the composition was 11.0. The composition was filled and sealed in a container with a lid made of Teflon (registered trademark) resin, and then placed in a thermostatic bath to perform a hydrothermal treatment under the following conditions.

[0140] Hydrothermal treatment temperature: 180℃

[0141] Hydrothermal treatment time: 72 hours

[0142] Hydrothermal treatment pressure: under autogenous pressure

[0143] After the hydrothermal treatment, a sufficient amount of pure water was added to the product cooled to room temperature and stirred to wash it. Then, the product was suction filtered using a filter paper with a pore size of 0.2 μm to obtain sodium manganese carbonate phosphate.

[0144] The obtained sodium manganese carbonate phosphate was dried at 110°C for 4 hours under vacuum and then crushed in a mortar to obtain the sodium manganese carbonate phosphate of this synthesis example. The purity of the sodium manganese carbonate phosphate Na3MnPO4CO3 of this synthesis example is 100% by weight, and no crystallized products other than Na3MnPO4CO3 are confirmed in its XRD spectrum. The Na3MnPO4CO3 of this synthesis example has a crystal grain size (WH diameter) of The lattice constant is a b is c is The compound has α of 90.00°, β of 90.16° and γ of 90.00°, a monoclinic crystal system, a sidorenkite-type (equivalent to sidorenkite-type) structure, and belongs to the space group P21 / m. The main XRD peaks are shown below.

[0145] (020) plane: 2θ = 26.44° relative intensity = 100

[0146] (220) plane: 2θ = 33.25° relative intensity = 100

[0147] (002) plane: 2θ = 34.68° relative intensity = 72

[0148] Synthesis Example 4 (Synthesis of Sodium Manganese Phosphate Carbonate)

[0149] Sodium carbonate (Na2CO3) and sodium manganese phosphate (olivine NaMnPO4) were mixed in a stoichiometric ratio of 1:1, and then mixed in a planetary ball mill under the conditions of Ar atmosphere, 600 rpm, and 12 hours. AB was added to the obtained powder in a manner to achieve a weight ratio of 15 wt%, and mixed in a planetary ball mill under the conditions of Ar atmosphere, 600 rpm, and 12 hours. AB was further added in a manner to achieve a weight ratio of 15 wt%, and mixed in a planetary ball mill under the conditions of Ar atmosphere, 400 rpm, and 3 hours, to obtain sodium manganese phosphate carbonate Na3MnPO4CO3.

[0150] Synthesis Example 5 (Synthesis of Sodium Nickel Phosphate Carbonate)

[0151] Nickel sulfate hexahydrate (NiSO4·6H2O), sodium phosphate 12hydrate (Na3PO4·12H2O), anhydrous sodium carbonate (Na2CO3) and anhydrous sodium sulfite (Na2SO3) are pulverized and mixed, and pure water is added thereto to obtain a composition having the following composition.

[0152] Nickel sulfate hexahydrate: 13.7 wt%

[0153] Sodium phosphate 12 hydrate: 19.6 wt%

[0154] Anhydrous sodium carbonate: 5.4% by weight

[0155] Pure water: Balance

[0156] The pH of the composition was 11.0. The composition was filled and sealed in a container with a lid made of Teflon (registered trademark) resin, and then placed in a thermostatic bath to perform a hydrothermal treatment under the following conditions.

[0157] Hydrothermal treatment temperature: 180℃

[0158] Hydrothermal treatment time: 16 hours

[0159] Hydrothermal treatment pressure: under autogenous pressure

[0160] After the hydrothermal treatment, a sufficient amount of pure water was added to the product cooled to room temperature and stirred, and the product was washed and then filtered using filter paper with a pore size of 0.2 μm to obtain sodium nickel carbonate phosphate.

[0161] The obtained sodium nickel carbonate phosphate was dried at 110°C for 4 hours under vacuum and then crushed in a mortar to obtain the sodium nickel carbonate phosphate of this synthesis example. The purity of the sodium nickel carbonate phosphate Na3NiPO4CO3 of this synthesis example is 100% by weight, and no crystallized products other than Na3NiPO4CO3 are confirmed in its XRD spectrum. The Na3NiPO4CO3 of this synthesis example has a grain size (WH diameter) of The lattice constant is a b is c is The compound has α of 90.00°, β of 89.29°, and γ of 90.00°, a monoclinic crystal system, a structure equivalent to that of the drenopyrite type, and belongs to the space group P21 / m. The main XRD peaks are shown below.

[0162] (020) plane: 2θ = 26.91° relative intensity = 96

[0163] (220) plane: 2θ = 33.68° relative intensity = 100

[0164] (002) plane: 2θ = 34.89° relative intensity = 88

[0165] Synthesis Example 6 (Synthesis of Sodium Cobalt Phosphate Carbonate)

[0166] Cobalt sulfate heptahydrate (CoSO4·7H2O), sodium phosphate 12hydrate (Na3PO4·12H2O) and anhydrous sodium carbonate (Na2CO3) were pulverized and mixed, and then pure water was added thereto to obtain a composition having the following composition.

[0167] Cobalt sulfate heptahydrate: 14.4 wt%

[0168] Sodium phosphate 12 hydrate: 19.4 wt%

[0169] Anhydrous sodium carbonate: 5.4% by weight

[0170] Pure water: Balance

[0171] The pH of the composition was 11.0. The composition was filled and sealed in a container with a lid made of Teflon (registered trademark) resin, and then placed in a thermostatic bath to perform a hydrothermal treatment under the following conditions.

[0172] Hydrothermal treatment temperature: 180℃

[0173] Hydrothermal treatment time: 16 hours

[0174] Hydrothermal treatment pressure: under autogenous pressure

[0175] After the hydrothermal treatment, a sufficient amount of pure water was added to the product cooled to room temperature and stirred to wash the product. The product was then suction filtered using filter paper with a pore size of 0.2 μm to obtain sodium cobalt phosphate carbonate.

[0176] The obtained sodium cobalt carbonate phosphate was dried at 110°C for 4 hours under vacuum and then crushed in a mortar to obtain the sodium cobalt carbonate phosphate of this synthesis example. The purity of the sodium cobalt carbonate phosphate Na3CoPO4CO3 of this synthesis example is 100% by weight, and no crystallized products other than Na3CoPO4CO3 are confirmed in its XRD spectrum. The Na3CoPO4CO3 of this synthesis example has a grain size (WH diameter) of The lattice constant is a b is c is The compound has α of 90.00°, β of 89.51°, and γ of 90.00°, a monoclinic crystal system, a structure equivalent to that of the drenopyrite type, and belongs to the space group P21 / m. The main XRD peaks are shown below.

[0177] (020) plane: 2θ = 26.88° relative intensity = 89

[0178] (220) plane: 2θ = 33.63° relative intensity = 94

[0179] (002) plane: 2θ = 34.85° relative intensity = 100

[0180] Example 1

[0181] The sodium iron phosphate carbonate Na3FePO4CO3 of Synthesis Example 1 was used as the positive electrode active material to prepare a sodium ion secondary battery (half cell) at 2 mA / cm 2 The charge and discharge test was carried out at room temperature at a current density of 1.50 V and a voltage ranging from -1.2 V to 1.3 V relative to the Ag / AgCl reference electrode. The discharge capacity of the first cycle was 134.3 mAh / g.

[0182] Example 2

[0183] A sodium ion secondary battery (half cell) was prepared in the same manner as in Example 1, except that the sodium iron phosphate carbonate Na3FePO4CO3 obtained in Synthesis Example 2 was used as the positive electrode active material, and a charge and discharge test was performed. The discharge capacity of the first cycle was 159.4 mAh / g.

[0184] Example 3

[0185] The sodium iron carbonate phosphate Na3FePO4CO3 obtained in Synthesis Example 2 was used as the positive electrode active material to prepare a sodium ion secondary battery (button battery). 2 The charge and discharge test was conducted at room temperature with a current density of 1.5 V and a cell voltage in the range of -1.2 to 1.3 V. The discharge capacity of the first cycle was 160.5 mAh / g.

[0186] Example 4

[0187] A sodium ion secondary battery (half cell) was prepared in the same manner as in Example 1, except that the sodium manganese carbonate phosphate Na3MnPO4CO3 obtained in Synthesis Example 4 was used as the positive electrode active material, and a charge and discharge test was performed. The discharge capacity of the first cycle was 134.5 mAh / g.

[0188] Example 5

[0189] A sodium ion secondary battery (half cell) was prepared in the same manner as in Example 1, except that the sodium cobalt phosphate carbonate Na3CoPO4CO3 obtained in Synthesis Example 6 was used as the positive electrode active material, and a charge and discharge test was performed. The discharge capacity of the first cycle was 141.2 mAh / g.

[0190] Reference example (non-aqueous sodium ion secondary battery)

[0191] The discharge capacity of a sodium ion secondary battery having a known non-aqueous electrolyte was measured by a method according to Japanese Patent No. 6270056.

[0192] A sodium ion secondary battery (button cell) having the following composition was prepared by the same method as in Example 1: the electrolyte was a non-aqueous electrolyte in which 1M sodium hexafluorophosphate (NaPF6) was dissolved in a mixed solvent containing ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, the positive electrode active material was the sodium iron phosphate carbonate Na3FePO4CO3 obtained in Synthesis Example 2, and the negative electrode was metallic sodium. 2 The charge and discharge test was conducted at room temperature with a current density of 1.5 V and a cell voltage in the range of 1.5 to 4.65 V. The discharge capacity of the first cycle was 128.0 mAh / g.

[0193] The operating voltage range of the reference example is above 3 V, which is wider than that of the embodiment. However, the discharge capacity is lower than that of the embodiment 3, so it can be seen that the aqueous sodium ion secondary battery of this embodiment shows a higher electrochemical capacity than the known non-aqueous sodium ion secondary battery.

[0194] Description of the mark

[0195] 1: Sodium ion secondary battery (button battery)

[0196] 2: Negative electrode cover

[0197] 3: Positive electrode container

[0198] 4: Negative electrode current collector

[0199] 5: Negative electrode mixture

[0200] 6: Positive electrode current collector

[0201] 7: Positive electrode mixture

[0202] 8: Isolation parts

[0203] 9: Space (electrolyte)

[0204] 10: Gasket

[0205] The entire contents of the specification, claims, abstract, and drawings of Japanese Patent Application No. 2019-098326 filed on May 27, 2019 are cited herein and incorporated as a disclosure of the specification of the present disclosure.

Claims

1. An aqueous sodium ion secondary battery, characterized in that: It has a positive electrode, a negative electrode, an electrolyte and a separator; the positive electrode has at least a general formula Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by MPO4CO3, wherein in the general formula, M is at least one selected from Fe, Mn, Ni and Co, and x is greater than 0 and less than 2; the aqueous sodium ion secondary battery has an aqueous electrolyte as the electrolyte.

2. The aqueous sodium ion secondary battery according to claim 1, characterized in that: The sodium transition metal polyanion has carbon on a part or all of its surface.

3. The aqueous sodium ion secondary battery according to claim 1, wherein: The crystal size of the sodium transition metal polyanion is Above and the following.

4. The aqueous sodium ion secondary battery according to claim 1, wherein: The aqueous electrolyte contains one or more selected from Na2SO4, NaNO3 and NaClO4.

5. The aqueous sodium ion secondary battery according to claim 1, wherein: The aqueous electrolyte contains NaClO4.

6. The aqueous sodium secondary battery according to claim 5, wherein: The electrolyte concentration in the electrolytic solution is 5 mol / kg or more.

7. The aqueous sodium ion secondary battery according to claim 1, wherein: The negative electrode contains at least NaTi2(PO4)3.

8. The aqueous sodium ion secondary battery according to any one of claims 1 to 7, wherein The positive electrode has at least a general formula of Na 3-x A positive electrode active material of a sodium transition metal polyanion represented by FePO4CO3, wherein in the general formula, x is greater than 0 and less than 2; the negative electrode contains at least NaTi2(PO4)3; and the aqueous electrolyte contains at least NaClO4.

9. General formula Na 3-x Use of the sodium transition metal polyanion represented by MPO4CO3 as a positive electrode active material in an aqueous sodium ion secondary battery, In the general formula, M is at least one selected from Fe, Mn, Ni and Co, and x is 0 or more and 2 or less. The aqueous sodium ion secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator. The aqueous sodium ion secondary battery includes an aqueous electrolyte as the electrolyte.

10. The use according to claim 9, wherein M contains at least Fe.

Citation Information

Patent Citations

  • High-speed printing apparatus in dot type serial printer

    JP1987070056A

  • Carbophosphates and related compounds

    JP2013520383A

  • Non-sealant airtight filter device

    JP2019098326A

  • Carbophoshates and related compounds

    CN102781826A

  • Lithium-based positive electrode material for sodion secondary battery, preparation method of lithium-based positive electrode material and sodion battery

    CN104466100A